Haemostatic actions of the folkloric medicinal plant extract Ankaferd Blood Stopper® - Aydin, Suleyman (My University, 2009)
[Abstract Not Available]
Keywords: Erythrocytes; Hemostatics; Plant Extracts; Plants, Medicinal; alpinia officinarum extract; ankaferd blood stopper; concanavalin A; glycophorin; Glycyrrhiza glabra extract; lectin; Nelumbo nucifera extract; oligosaccharide; phytohemagglutinin; plant extract; ricin; thymus extract; unclassified drug; Urtica dioica extract; Vitis vinifera extract; ankaferd blood stopper; hemostatic agent; plant extract; blood group typing; drug activity; hemagglutination; in vitro study; letter; medicinal plant; chemistry; drug effect; erythrocyte; note